IMPLEMENTASI KONSEP MUROBBI DALAM BIMBINGAN KONSELING SANTRI DI PONDOK PESANTREN DARUL AMANAH BEDONO JAMBU KABUPATEN SEMARANG - Mustafidin, Ahmad; Andi, Andi Wahyudi; Ambari, M. Zaki; Ma’fudin, Alif (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
Recently, the education system has transformed with the integration of Islamic boarding schools and formal education, known as the modern Islamic boarding school education system. Each institution has its own issues, but they prioritize Quran memorization, foreign languages, leadership, management, teaching materials, parenting, local culture, and religion. This study aims to examine the Murobbi superior program at Darul Amanah Bedono Islamic Boarding School in Semarang Regency. Quoting from Abdul Rahman's essay entitled "The Concept of Murabbi in the Qur'an" Ibnu Jauzī found that the importance of knowledge lies in the disclosure of a murabbī. The author uses a qualitative descriptive method in this study to collect secondary data from journals, books, theses, and websites, along with data and researcher triangulation. The results of this research are based on the theory of counseling guidance services through murobbi, from here the word "murobbi" becomes a new term used instead of the word "caregiving". From this, the Murobbi concept from the perspective of Islamic education which is applied in the education system at the Darul Amanah Bedono Islamic Boarding School institution is very effective and efficient, because it is not only the students who receive lessons, but the Murobbi also gain new experience and knowledge regarding, 1) how to educate , 2) fostering, 3) nurturing, and 4) supervising students. The results suggest that using the Murobbi concept in counseling is beneficial due to its positive impact on guiding, caring, educating, and learning.